Solid-state characterization and impurities determination of fluconazol generic products marketed in Morocco - Houda Bourichi; Youness Brik; Philipe Hubert; Yahia Cherrah; Abdelaziz Bouklouze (Elsevier, 2012)
In this paper, we report the results of quality control based in physicochemical characterization and impurities determination of three samples of fluconazole drug substances marketed in Morocco. These samples were supplied by different pharmaceuticals companies. The sample A, as the discovered product, was supplied by Pfizer, while samples B and C (generics), were manufactured by two different Indian industries. Solid-state characterization of the three samples was realized with different physicochemical methods as: X-ray powder diffraction, Fourier-transformation infrared spectroscopy, differential scanning calorimetry. High performance liquid chromatography was used to quantify the impurities in the different samples. The results from the physicochemical methods cited above, showed difference in polymorph structure of the three drug substances. Sample A consisted in pure polymorph III, sample B consisted in pure polymorph II, sample C consisted in a mixture of fluconazole Form III, form II and the monohydrate. This result was confirmed by differential scanning calorimetry. Also it was demonstrated that solvents used during the re-crystallization step were among the origins of these differences in the structure form. On the other hand, the result of the stability study under humidity and temperature showed that fluconazole polymorphic transformation could be owed to the no compliance with the conditions of storage. The HPLC analysis of these compounds showed the presence of specific impurities for each polymorphic form, and a possible relationship could be exist between impurities and crystalline form of fluconazole. Keywords: Generic product, Quality control, Fluconazole, Polymorphism, Impurities